2023
DOI: 10.3390/en16176301
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Offshore Hydrogen Production from Wind Farms in the Baltic Sea Area—A Study Case for Poland

Klaudia Ligęza,
Mariusz Łaciak,
Bartłomiej Ligęza

Abstract: In Poland, hydrogen production should be carried out using renewable energy sources, particularly wind energy (as this is the most efficient zero-emission technology available). According to hydrogen demand in Poland and to ensure stability as well as security of energy supply and also the realization of energy policy for the EU, it is necessary to use offshore wind energy for direct hydrogen production. In this study, a centralized offshore hydrogen production system in the Baltic Sea area was presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A techno-economic evaluation of offshore wind-to-hydrogen scenarios conducted in the UK by Giampieri et al [47] showed that compressed hydrogen produced offshore is the most cost-effective scenario and stated that the economic feasibility is greatly affected by the storage period and the offshore wind farm distance to the shore. Also, the high annual capacity factor of offshore wind farms makes the use of offshore wind for hydrogen production advantageous as well and can help with affordable hydrogen production [48]. Additionally, through modeling appeared to lower the cost of producing hydrogen, techno-economic cost model analysis, showed that with the scaling of offshore wind farms, the long-term outlook for the LCoH declined towards £2/kg of hydrogen for fixed bottom offshore wind turbines [49].…”
Section: Electrolyzer Integration With Offshore Windmentioning
confidence: 99%
“…A techno-economic evaluation of offshore wind-to-hydrogen scenarios conducted in the UK by Giampieri et al [47] showed that compressed hydrogen produced offshore is the most cost-effective scenario and stated that the economic feasibility is greatly affected by the storage period and the offshore wind farm distance to the shore. Also, the high annual capacity factor of offshore wind farms makes the use of offshore wind for hydrogen production advantageous as well and can help with affordable hydrogen production [48]. Additionally, through modeling appeared to lower the cost of producing hydrogen, techno-economic cost model analysis, showed that with the scaling of offshore wind farms, the long-term outlook for the LCoH declined towards £2/kg of hydrogen for fixed bottom offshore wind turbines [49].…”
Section: Electrolyzer Integration With Offshore Windmentioning
confidence: 99%